Analisis Kelayakan Bisnis Kue Kering “Phianz Cookies” di Kecamatan Kademangan, Kota Probolinggo (Feasibility Analysis of Pastry Business “Phianz Cookies” in Kademangan District, Probolinggo City) - Pratama, Triyan Bayu; Oktaviani, Dewi Anggun; Lidyana, Novita (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2025)
The